If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 61 = 6x + -11 Reorder the terms: 61 + 3x = 6x + -11 Reorder the terms: 61 + 3x = -11 + 6x Solving 61 + 3x = -11 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 61 + 3x + -6x = -11 + 6x + -6x Combine like terms: 3x + -6x = -3x 61 + -3x = -11 + 6x + -6x Combine like terms: 6x + -6x = 0 61 + -3x = -11 + 0 61 + -3x = -11 Add '-61' to each side of the equation. 61 + -61 + -3x = -11 + -61 Combine like terms: 61 + -61 = 0 0 + -3x = -11 + -61 -3x = -11 + -61 Combine like terms: -11 + -61 = -72 -3x = -72 Divide each side by '-3'. x = 24 Simplifying x = 24
| 245-2x=43x+15 | | 5x-x=14*5 | | 6.7=-3.2+x | | 159-4x=23x+15 | | a=bc+d | | 96=5x^2-x^2 | | 41-7x=90 | | 1-5x-36x^2=0 | | 4x+1y=6 | | 3u^2-27= | | 2/1= | | 16-10w=-74 | | x-(x^2)=1 | | 5x+2x+x=8x^3 | | 5x+2x+x=8x | | 1/1= | | 64x=16x^3 | | 5x+2x+x=8 | | u^2+8u+16= | | 486=27r | | 1/-2= | | 17=1p-3-3p | | 3x-3y=15 | | a/4+3=-3 | | (x-2)(x+3)(3x+1)=0 | | 2x-80+x-50+13x+30=180 | | k/3-3=-11 | | v+8=13 | | 6x+10+14x=5x(1+4x) | | -1+2= | | m/7-9=5 | | z=2ab |